Navigating Collaboration: Newcomer Parents’ Perceptions and Experiences with Norwegian Schools - Sultana Ali Norozi; Nassira Essahli Vik (Social Sciences)
This qualitative study explores the perceptions and experiences of six newcomer parents from different countries (Afghanistan, Syria, Iran, Chile, Russia, and Ukraine) regarding their collaboration with Norwegian schools. Semi-structured in-depth interviews, ranging from 55 to 80 min, were conducted in participants’ native languages and English. Thematic analysis was employed to analyze the data. Four major themes emerged, as follows: (1) “Journeying Through Integration within the Norwegian Educational Landscape”; (2) “Collaboration: Dialogic or Monologic?”; (3) “Language and Communication Barriers”; and (4) “Navigating New Horizons”. The findings highlight that despite the challenges, participants expressed appreciation for the support they received from schools and teachers. The findings also indicate the need for schools to improve communication and cultural understanding to foster meaningful collaboration with newcomer parents. Schools must also provide more opportunities for parent involvement in decision-making processes. This study adds to the limited literature on newcomer parents’ perspectives on school collaboration and provides insights for policymakers, educators, and school administrators to enhance the educational experiences of newcomer students and their families in Norway.